The Research of Correlation Between Blood Pressure and Nailfold Capillary Parameters in Exercising and Non-Exercising Pregnant Women - Ljubojević, Vesna; Bojanić, Vlatka; Nožica-Radulović, Tatjana; Draganović, Dragica; Skočić-Smoljanović, Saša (Scripta Medica, 2022)
Introduction: With an increase in cardiac output, blood pressure values in pregnancy increase. The aim of the study was to examine the effect of prenatal exercises on the circulatory parameters and the correlation between blood pressure and nailfold capillary parameters in healthy pregnant women. Methods: The blood pressure, shape, and length of nailfold capillary were assessed in 35 non-exercising pregnant women and 35 pregnant women who exercised, at the beginning of the study (between 20 and 32 gestational weeks) and the end of the study (28 - 40). Results: The elevation in blood pressure was significantly lower in pregnant women who exercised in relation to non-exercising pregnant women. After eight weeks, the length of the capillary loops increased by 30 µm, and the number of pregnant women with pronounced shape changes of capillary loops increased, with no difference between the groups. Non-exercisers had a correlation between the change in diastolic pressure and the increase in capillary length (r=0.53, p=0.001). In the experimental group, the correlation between the change in blood pressure and the increase in the length of capillary loops was not determined. Conclusion: Prenatal physical activity had a beneficial impact on the circulation of pregnant women. In pregnant women in the third trimester, after eight weeks of follow-up, the length of the nailfold capillary loops and the presence of pronounced shape changes of capillary loops were increased, without difference between exercisers and non-exercisers. In non-exercising pregnant women, the capillary length increases with the elevation of diastolic blood pressure, while the correlation was not found in pregnant women who exercised.